2019
DOI: 10.3389/fmicb.2019.00926
|View full text |Cite
|
Sign up to set email alerts
|

Roots Mediate the Effects of Snowpack Decline on Soil Bacteria, Fungi, and Nitrogen Cycling in a Northern Hardwood Forest

Abstract: Rising winter air temperature will reduce snow depth and duration over the next century in northern hardwood forests. Reductions in snow depth may affect soil bacteria and fungi directly, but also affect soil microbes indirectly through effects of snowpack loss on plant roots. We incubated root exclusion and root ingrowth cores across a winter climate-elevation gradient in a northern hardwood forest for 29 months to identify direct (i.e., winter snow-mediated) and indirect (i.e., root-mediated) effects of wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Another study found that winter snowpack decline associated with global warming increased bacterial richness and phylogenetic diversity (2016). However, any effects of changing soil climate conditions may have been mediated by effects on root growth, which is impaired by soil freezing associated with the snowpack decline (Sorensen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that winter snowpack decline associated with global warming increased bacterial richness and phylogenetic diversity (2016). However, any effects of changing soil climate conditions may have been mediated by effects on root growth, which is impaired by soil freezing associated with the snowpack decline (Sorensen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, shrubs have been shown to affect microbial communities in some ecosystems (Collins et al, 2018;Gorzelak et al, 2012) as a result of alleviating understorey microenvironments. Therefore, microbes might be good candidates and several studies have already assessed changes in microbial communities in winter (Fournier et al, 2020;Sorensen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, shrubs have been shown to affect microbial communities in some ecosystems (Collins et al, 2018; Gorzelak et al, 2012) as a result of alleviating understorey microenvironments. Therefore, microbes might be good candidates and several studies have already assessed changes in microbial communities in winter (Fournier et al, 2020; Sorensen et al, 2019). For example, Sorensen et al (2019) have shown that tree roots cannot buffer elevation effect on bacterial richness in winter, but may buffer elevation effects on bacterial β ‐diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate characterization of the activity of soil microbiomes is key to understanding how the soil compartment functions and responds to chronic and acute perturbations ( Bardgett and van der Putten, 2014 ; Delgado-Baquerizo et al, 2019 ). Snowpack dynamics for example are strongly influenced by climate driving forces such as atmospheric warming and precipitation patterns, and in turn regulate both plant and microbial activity ( Brooks et al, 1998 ; Lipson et al, 2002 ; Steltzer et al, 2009 ; Wipf, 2010 ; Sorensen et al, 2019 ). Our prior work observed that snowmelt induced a significant shift in soil water potential, dynamic biomass growth and turnover that corresponded to a reassembly of the soil microbiome ( Sorensen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%